Microbial indicators of diesel fuel toxicity in polar soils - Van Dorst, Josie (UNSW Sydney, 2014)
Petroleum hydrocarbon contamination is extensive throughout the Polar Regions and particularly prevalent around areas of concentrated anthropogenic activity. Whilst toxicity information is limited there is evidence to suggest that petroleum hydrocarbon contamination is more damaging near the poles than in temperate regions due to the low temperatures, low nutrient availability and extended exposure to the contaminants. As the dominant biota present in Antarctic soils, microbial populations are ideal candidates for the development of site-specific ecotoxicology assays. Bacteria in particular are valuable indicators of ecosystem health due to their pivotal role in biogeochemical cycles, nutrient cycling and ecosystem sustainability. For this thesis I have examined the response of the indigenous soil microbial community to diesel fuel toxicity at the sub-Antarctic Macquarie Island. I have employed a range of techniques to characterise the community including novel culturing, community fingerprinting, pyrosequencing and qPCR methods. A range of broad community indices and specific functional portions of the community were targeted to establish the most promising microbial indicators of diesel fuel toxicity. Similar approaches were then applied to three chronically contaminated sites under active remediation to monitor the microbial community recovery. The diversity, species richness, species evenness and similarity indices declined with increasing diesel fuel concentrations. Yet, the greatest response of the diesel fuel was to alter relative abundances of key lineages rather than remove entire species. This response was consistent across all soils but varied in the severity of the response between locations. Key processors within the nitrogen cycle were also inhibited but again the severity of the response was site-specific, highlighting the need for site-specific remediation targets to be established.